WIND: Semantics of the Symbol in Boris Pasternak’s Novel “Doctor Zhivago” - Irina V. Yakushevich (RUDN Journal of Language Studies, Semiotics and Semantics, 2023)
The study was conducted at the intersection of semiotics, linguoculturology and linguopoetics of the text and is devoted to one of the urgent issues - the identification, semantic description and linguistic representation of one of the significant symbols of national mythological thinking - WIND. The purpose of the study is to present a model of the symbolic structure of the symbol WIND and to consider its linguistic transformation in the novel «Doctor Zhivago». The main research method is a semantic-semiotic description of the symbolic structure of the symbol WIND in the categories of signifier A and signified B. By symbol’s semantics we mean the peculiarities of its linguistic embodiment and, as a consequence, the emergence of the author’s transformation of the general cultural symbolic code of a word. The signifier of the symbol - the sensual image of the air flow - in the text can be semanticized both by the words wind, blizzard, storm, etc., and by different syntactic constructions. The signified is a number of symbolic meanings which have developed in the culture of the people as a result of the mythological identification of the air element of nature and man. As a result of the study, five symbolic meanings were found, for the objectification of which dictionary data and folklore texts were used: 1) WIND→SPIRIT, SOUL, 2) WIND→ BIRTH AND DEATH OF A PERSON, 3) WIND→WORD, MESSAGE, 4) WIND→EVIL, MAGIC, 5) WIND→LIFE. In the text, each of these general cultural meanings is transformed into a system of events and characters of the novel. So, the second meaning is represented by four variants of the signified: ‘death of Zhivago’s mother’, ‘birth of a son’, ‘death of Antipov’, ‘death of Yuri Zhivago’. The most frequent in the representation of the two-component structure of the symbol are ascending gradation series, indicating the growth of wind power and its transformation into rain or blizzard. At the same time, a gradation series of words unfolds, conveying the dynamics of the psychological or physical state of the hero. The symbolic meaning is often actualized with the help of other symbols whose signified duplicates the wind symbol. The result of the study is the conclusion about the ambivalent nature of the symbol WIND, which occurs at key moments in the of Yuri Zhivago’s life. The wind is life itself in its mystical understanding like immortality.